Synthesis, antioxidant activity, and HPLC enantioseparation of aryloxyaminopropanols derived from naphthalen-2-ol - Čižmáriková R.; Habala L.; Valentová J.; Némethy A.; Bruchatá K; Hroboňová K. (Sciendo, 2023)
The present work describes the synthesis, physico-chemical characteristics, antioxidative properties, and high-performance liquid chromatography (HPLC) enantioseparation of novel, potentially bioactive aryloxyaminopropanols - derivatives of naphthalen-2-ol modified in the basic part of their molecules. Reaction of naphthalene-2-ol with chloromethyloxirane leads to 2-[(naphthalen-2-yloxy)methyl]oxirane, which reacts in the next step with branched aliphatic amines (isopropylamine, tert-butylamine, and dimethylamine), aromatic amines (aniline, 3,4-dimethoxyphenylethylamine), and heterocyclic amines (pyrrolidine, imidazole, 2-methylimidazole, piperidine, morpholine, 4-methylpiperidine, or 2-methoxyphenylpiperidine). The target compounds were isolated in the form of free bases, as well as their salts with fumaric or hydrochloric acid. Their purity was established by thin-layer chromatography and their IR, UV, 1H-NMR, and 13C-NMR spectra were recorded. The antioxidant activities of prepared compounds were measured by the 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) method and they were compared with the values for the corresponding salts. Enantioseparation was accomplished by means of enantioselective HPLC using amylose tris(3,5-dimethylphenyl)carbamate (Chiralpak AD), as well as Chirobiotic T (native teicoplanin) in some cases.